Visual Arts Lessons and the Role of Innovative Pedagogical Approaches in Developing Students’ Aesthetic Taste - Boboniyozova Roziya Mirsalim qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the theoretical and practical aspects of employing innovative pedagogical approaches in visual arts lessons to develop students’ aesthetic taste. The study emphasizes the effectiveness of modern teaching technologies, such as the flipped classroom, interactive methods, and competency-based approaches, in fostering students’ appreciation of beauty, artistic perception, and creative thinking. Drawing on the research of Shovdirov S.A. and other scholars, the article demonstrates how the integration of innovative methods enhances students’ artistic competencies and nurtures their aesthetic sensibility in contemporary educational settings.